Taxonomic significance of leaf micromorphology in some selected taxa of Acanthaceae (Peninsular Malaysia) - Che Amri, Che Nurul Aini; Talip, Noraini; Mohamad, Abdul Latiff; Ahmad Juhari, Muhammad Amirul Aiman; Abdul Rahman, Mohamad Ruzi; Sharif, Idris (AIP Publishing, 2014)
Comparative leaf micromorphology study was conducted in eight taxa of Acanthaceae from Peninsular Malaysia. Eight chosen taxa were Acanthus ebracteatus Vahl, A. ilicifolius L., A. volubilis Wall, A. montanus T. Anderson, Andrographis paniculata (Burm.f.) Wall. ex Nees, Asystasia gangetica subsp. micrantha (Nees) Ensermu, Chroesthes longifolia (Wight) B. Hansen and Peristrophe roxburghiana (Schult.) Bremek. The objective of this study was to identify the leaf micromorphological characteristics that can be used in species identification and also as supportive data in classification. The procedures involved such as dehydration, critical point drying, gold coated and examination under scanning electron microscope. Findings in this study have demonstrated the similarities and variations in leaf micromorphological characteristics such as in type of epicuticular waxes, cuticular ornamentations, stomata characteristics and in the presence of trichomes. Six types of epicuticular waxes and five types of trichomes were observed. Variations in cuticular ornamentations and stomata structure can be used to differentiate species. One diagnostic character was found and proven to be very useful to identify Acanthus via the presence of simple trichomes (short-conicle like). In conclusion, the results of this study have shown that leaf micromorphological characteristics have taxonomic significance that can be useful in classifications and identification especially at species level.